Impact of Cash Flow Coverage, Debt Service & Current Ratio on Capital Structure Decisions: Empirical Evidence from the Indian Corporate Sector - Rasoolpur, Gurnam Singh (Journal of Research in Marketing (ISSN: 2292-9355), 2014)
This empirical study examines the capital structure decisions of developing countries through a case study of Indian corporate sector by classifying the capital structure of 298 out of top 500 private sector manufacturing firms selected on the basis of sales turnover for the year 2004-2005 which covers a time span of eleven years commencing from 1995-96 to 2005-06 by cash flow coverage ratio, debt service ratio and current ratio. The study reveals that larger number of companies is distributed, for all the variables under study, in 0-100 percent capital structure range during 1995-96 (55 to 55.93 percent) and 2005-06 (62.68 to 63.29 percent), respectively. It is found that lesser number of companies is distributed, for all the variables under study, in 200-300 percent and more than 300 percent capital structure ranges during 1995-96 (3.93 to 4.06 percent each) and 2005-06 (7.32 to 7.39 percent and 3.48 to 3.52 percent), respectively. Overall, there is a shifting of companies from higher capital structure ranges towards lower capital structure ranges during the study period. Cash flow coverage ratio, debt-service ratio and current ratio are showing negative relationship with capital structure, implying less use of debt when these variables attain a higher value during 1995-96 and 2005-06, respectively.